AB0133 Role of Monocytes Subsets in the Atherothrombosis and Endothelial Dysfunction Associated with Rheumatoid Arthritis: Beneficial Effects of Tocilizumab. (9th June 2015) - Barbarroja, N.; Ruiz-Limon, P.; Perez-Sanchez, C.; Jimenez-Gomez, Y.; Abalos-Aguilera, M.; Font, P.; Aguirre, M.; Segui, P.; Calvo, J.; Ortega, R.; Collantes-Estevez, E.; Escudero, A.; et al.
Abstract : Background: Monocytes play a key role in the pathogenesis of the atherothrombosis. It has been described three subsets of monocytes with different actions in the vascular pathology: MON1 (CD14brightCD16-), MON2 (CD14dimCD16bright) and MON3 (CD14brightCD16bright). The distribution of these monocytes subsets and its profile associated with cardiovascular disease (CVD) in rheumatoid arthritis (RA) remain unravelled. Tocilizumab (TCZ) is a new therapeutic drug, very effective in RA, but its effects on CVD are still unknown. Objectives: 1) To functionally characterize the different monocytes subsets in RA patients and analyze their role in the endothelial dysfunction, altered oxidative status and proinflammatory/prothrombotic profile associated to RA. 2) To evaluate the effect of TCZ in the proatherotrombotic profile of these cells and its association with the clinical outcome. Methods: Thirty RA patients and 15 healthy donors were included. Endothelial function was measured through post occlusive hyperaemia using Laser-Doppler. Carotid intima media thickness (CIMT) was used as atherosclerosis marker. MON1, MON2 and MON3 were characterized by flow cytometry and isolated using immuno-magnetic selection. Different proinflammatory cytokines, peroxides levels and cellular activation markers were analyzed in the three different subsets. Selected RA patients (10) received 162 mg/week subcutaneous TCZ. Blood samples were collected before and after 6 months of treatment. Results: CD16+ (MON2-MON3) monocytes were significantly extended in RA patients. These subsets had increased protein expression of proinflammatory cytokines, markers of cellular activation and peroxide levels. RA patients had impaired endothelial function, with a reduced perfusion value after ischemia. Increased MON2 and MON3 and reduced MON1 percentage were associated with a pathologic CIMT thickness. Clinical parameters such as evolution time, C reactive protein, anti-CCPs antibodies and rheumatoid factor levels strongly correlated with endothelial dysfunction, decreased percentage of MON1 monocytes and increased number of MON2 and MON3 subsets. Furthermore, higher expression of proinflammatory/prothrombotic molecules and endothelial adhesion markers in these CD16+ cells correlated with the alteration in endothelial function and the clinical parameters. After 6 months of treatment, TCZ reduced clinical parameters of inflammation, autoinmunity and joint damage. Endothelial function was significantly restored. TCZ reduced the expression of inflammatory and prothrombotic molecules, peroxide and peroxinitrite levels. The reduction of proinflammatory cytokines and oxidative stress in RA monocytes significantly correlated with the improvement of the joint damage and endothelial function. Conclusions: 1) RA patients display an increased number of MON2 and MON3 monocytes directly associated to the autoimmune and inflammatory profile, the progression of the disease and the altered microvascular function, indicating that CD16+ subpopulation might play a key role in the CVD pathogenesis associated with RA. 2) TCZ induces an improvement of the proatherothrombotic profile in RA patients. Acknowledgements: Funded by CTS7940, PI12/01511, PI2013-0191, SER Disclosure of Interest: None declared